A FACS-based novel isolation technique identifies heterogeneous CTCs in oral squamous cell carcinoma - Chauhan, Anshika; Pal, Arnab; Sachdeva, Meenakshi; Boora, Geeta S.; Parsana, Monil; Bakshi, Jaimanti; Verma, Roshan Kumar; Srinivasan, Radhika; Chatterjee, Debajyoti; Maitra, Arindam; Ghoshal, Sushmita (Frontiers in Oncology, 2024)
Purpose: Isolating Circulating Tumor Cells (CTCs) from the blood is challenging due to their low abundance and heterogeneity. Limitations of conventional CTC detection methods highlight the need for improved strategies to detect and isolate CTCs. Currently, the FDAapproved CellSearch TM and other RUO techniques aren't available in India. Therefore, we wanted to develop a flexible CTC detection/isolation technique that addresses the limitation(s) of currently available techniques and is suitable for various downstream applications.We developed a novel, efficient, user-friendly CTC isolation strategy combining density-gradient centrifugation and immuno-magnetic hematogenous cell depletion with FACS-based positive selection using multiple CTC-specific cell-surface markers. For FACS, a stringent gating strategy was optimised to exclude debris and doublets by SCC/FSC discriminator, remove dead cells by DAPI staining, and eliminate non-specific fluorescence using a "dump" channel. APC-labelled antiCD45mAB was used to gate remaining hematogenous cells while multiple epithelial markers (EpCAM, EGFR, Pan-Cytokeratin) and an EMT marker (Vimentin) labelled with FITC were used to sort cancer cells. The technique was initially developed by spiking Cal27 cancer cells into the blood of healthy donors and then validated in 95 biopsy-proven Oral Squamous Cell Carcinoma (OSCC) patients. CTCs isolated from patients were reconfirmed by Giemsa-staining, immuno-staining, and whole transcriptome amplification (WTA), followed by qRT-PCR. In-vitro culture and RNA sequencing were also performed to confirm their suitability for various downstream applications.The mean detection efficiency for the Cal27 tongue cancer cells spiked in the whole blood of healthy donors was 32.82%± 12.71%. While ~75% of our patients (71/95) had detectable CTCs, the CTC positivity was independent of the TNM staging. The isolated potential cancer cells from OSCC patients were heterogeneous in size. They expressed different CTC-specific markers in various combinations as identified by qRT-PCR after WTA in different patients. Isolated CTCs were also found to be suitable for downstream applications like short-term CTC culture and RNAseq.We developed a sensitive, specific, flexible and affordable CTC detection/isolation technique, scalable to larger patient cohorts, provides a snapshot of CTC heterogeneity, isolates live CTCs ready for downstream molecular analysis and, most importantly, is suitable for developing countries.